2020
DOI: 10.1002/jcla.23544
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel variants in Iranian consanguineous pedigrees with nonsyndromic hearing loss by next‐generation sequencing

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…In summary, GIPC3 mutations have been shown to underlie NSHL associated with DFNB15 , DFNB72 and DFNB95 . In NSHL, biallelic, nonsense, and shift mutations were also observed in the GIPC3 gene ( Chen et al, 1997 ; Ain et al, 2007 ; Charizopoulou et al, 2011 ; Rehman et al, 2011 ; Diaz-Horta et al, 2012 ; Sirmaci et al, 2012 ; Ramzan et al, 2013 ; Petrova et al, 2021 ), and more GIPC3 mutation loci are gradually being reported as research progresses ( Siddiqi et al, 2014 ; Ammar-Khodja et al, 2015 ; Asgharzade et al, 2018 ; Khan et al, 2019 ; Bitarafan et al, 2020 ; Kannan-Sundhari et al, 2020 ; Zhou et al, 2020 ; Table 1 ).…”
Section: Effects Of Gipc3 Mutations On the Auditor...mentioning
confidence: 99%
“…In summary, GIPC3 mutations have been shown to underlie NSHL associated with DFNB15 , DFNB72 and DFNB95 . In NSHL, biallelic, nonsense, and shift mutations were also observed in the GIPC3 gene ( Chen et al, 1997 ; Ain et al, 2007 ; Charizopoulou et al, 2011 ; Rehman et al, 2011 ; Diaz-Horta et al, 2012 ; Sirmaci et al, 2012 ; Ramzan et al, 2013 ; Petrova et al, 2021 ), and more GIPC3 mutation loci are gradually being reported as research progresses ( Siddiqi et al, 2014 ; Ammar-Khodja et al, 2015 ; Asgharzade et al, 2018 ; Khan et al, 2019 ; Bitarafan et al, 2020 ; Kannan-Sundhari et al, 2020 ; Zhou et al, 2020 ; Table 1 ).…”
Section: Effects Of Gipc3 Mutations On the Auditor...mentioning
confidence: 99%
“…Although more than 500 genes are predicted to be responsible for the function faultlessly of the auditory system, only 180 genes causing HL have been identi ed, to date (Ajam-Hossieni et al, 2022). Genetic factors account for almost half of the reports related to hearing impairment, and more than two-thirds of these cases appear as a single symptom and without any other defect under the name of non-syndromic hearing loss (NSHL) (Bitarafan et al, 2020). About 80% of NSHL is inherited in autosomal recessive, while approximately one-fth of cases are autosomal dominant.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that congenital hearing loss affects 1-2 per 1000 individuals of the Western population while in the Iranian population it reaches one in 166, making it the second most common disorder after intellectual disability (6). This relatively high frequency of HL may be described by a high rate of consanguineous marriages, 38% on average, among the Iranian population because of several factors like their culture, tradition, and religion (7). Studies showed that more than two-thirds of congenital hearing loss is caused by genetic factors (8).…”
Section: Introductionmentioning
confidence: 99%